A Code Excited Linear Predictive coding algorithm for real-time implementation - Nel, Izak H. J.(Izak Hendrik Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng.) -- University of Stellenbosch, 1989.